A Novel Management Platform Based on Personalized Home Care Pathways for Medicine Management and Rehabilitation of Persons With Parkinson's Disease—Requirements and Implementation Plan of the Care-PD Program - Gao, Song; Hou, Yuning; Ma, Renyan; Kaudimba, Keneilwe Kenny; Jin, Lingjing; Wang, Han; Wang, Ru (Frontiers in Neurology, 2021)
As the proportion of the aging population increases, the incidence of Parkinson’s disease (PD) in China is increasing year by year. PD is both public health and social problem that the government and the whole society are facing. Persons with PD need reasonable medication management and rehabilitation strategies after a clear diagnosis. A proper home care plan can effectively slow the progression of PD. However, Persons with PD lack an effective way to manage their illnesses and cannot achieve the recommended clinical path in a family environment. Medication management, condition monitoring, and rehabilitation training are important components of the home care plan for PD. Persons with PD requires strategies that delay the development of the disease, adhere to treatment, and optimize the quality of life. Thus, we developed a small program called Care-PD. The development of the care-PD is funded by the National Key R&D Program of China (No. 2018YFC1314700), to build a medicine management and service platform for PD. It is a multi-dimensional model designed for PD, including services such as medication management, symptom monitoring, professional counseling, home life, and community communication. The Care-PD can become a key technology that increases the compliance of persons with PD with home care plans and improve measures to control the disease. In this article, we describe the medication management and services for PD based on the Care-PD program and its structure. The small program will improve the adverse conditions faced by persons with PD via combining the latest technology and clinical approaches. Meanwhile, we describe a verification strategy to evaluate the effectiveness of the Care-PD program as a medication management and service platform for PD.